2018
DOI: 10.1111/aos.13994
|View full text |Cite
|
Sign up to set email alerts
|

Novel BEST1 mutations and special clinical characteristics of autosomal recessive bestrophinopathy in Chinese patients

Abstract: Purpose: The aim of this study was to describe the genetic and clinical characteristics of Chinese patients with autosomal recessive bestrophinopathy (ARB). Methods: This study presents a retrospective observational case series. Twentyone ARB patients and 25 clinically healthy family members were recruited. The coding regions and adjacent intronic regions of BEST1 were analysed via Sanger sequencing. Clinical examinations, including ultrasound biomicroscopy, A-scan, optical coherence tomography, fundus autoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
3
23
1
Order By: Relevance
“…Seven variants in BEST1 were detected, including one novel mutation. Missense mutations were the most common mutation type, which was consistent with previous studies [10,14]. Interestingly, we also observed that 4 out of 7 mutations identified in this study were located in exon 5, which is similar to other studies where 53.85% of mutations were located in exons 5 or 7 [12].…”
Section: Discussionsupporting
confidence: 93%
“…Seven variants in BEST1 were detected, including one novel mutation. Missense mutations were the most common mutation type, which was consistent with previous studies [10,14]. Interestingly, we also observed that 4 out of 7 mutations identified in this study were located in exon 5, which is similar to other studies where 53.85% of mutations were located in exons 5 or 7 [12].…”
Section: Discussionsupporting
confidence: 93%
“…BVMD is clinically characterized by morphologic variability: the deposition of yellowish, lipofuscin‐like or vitelliform lesions usually evolves through previtelliform, vitelliform with “egg‐yolk,” pseudohypopyon, vitelliruptive with scrambled egg and atrophic stages . Although ARB is considered as a null phenotype of bestrophin‐1 in humans, it displays serous retinal detachment with extramacular vitelliform lesions and it is likely that this form affects the eye development more than BVMD . The most common distinguishing characteristic of ARB is the deposits in the extra foveal and extra macular subretinal matrix…”
Section: Introductionmentioning
confidence: 99%
“…6 Nearly 40 biallelic mutations in BEST1 have been reported in ARB patients to date. [12][13][14][15] Retinopathy includes an irregularity of the RPE throughout the posterior fundus with punctate flecks, which is easily seen on autofluorescence imaging. Retinal edema and subretinal fluid are common findings on OCT imaging.…”
Section: Introductionmentioning
confidence: 99%